The effect of Self-Care Program Base on the Orem Frame Work on Fatigue and Activity of Daily Living in Multiple Sclerosis Patients - Reza Masoudi; Fereidoun Kheiri; Fazllollah Ahmadi; Issa Mohammadi (University of Social Welfare and Rehabilitation Sciences, 2009)
Objective: Fatigue is one of the tormentest symptom of the Multiple Sclerosis that decrease self care ability and role performance of patients and potential of activity of daily living. The purpose of this study was to assess the effect of Orem self- care program on fatigue and activity of daily living (ADL) in Multiple Sclerosis clients. Materials & Methods: This quasi experimental study was a clinical trial research that was done on seventy multiple sclerosis patients whom were selected randomly from M.S. association and assigned to experimental and control group by balanced randomized method. The experimental group was treated with 8 sessions of self-care program based on Orem self-care framework and the program belonged for three months in experimental group and followed up with self-report questionnaire. Score of fatigue and activity of daily living of two groups were assessed at first of research and three months later by Payper and Barthel scales. Data were analyzed using Chi square, Independent T and Paired T test and Variance analysis. Results: There was no significant difference between two group in fatigue (P=0.48) and activity of daily living (P= 0.24) befor intervention, but these differences were significant after intervention (P<0.001). There were significant differences in experimental group between before and after score of fatigue and ADL (P<0.001), whereas there was no significant difference in fatigue (P=0.086) and ADL (P=0.33) of control group. Conclusion: Utilizing self care program base on the Orem frame work and the educational needs as a safe and inexpensive nursing intervention, it might be effective on fatigue decrease and activity of daily living enhance in Multiple Sclerosis patients.